Effects of machining characteristics on electrical discharge machining using different types of electrode materials - M. S., Reza; Khairul Anuar; S. H., Tomadi; M. A., Hassan; W. S. W., Harun (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.